Molecular changes in premenopausal oestrogen receptor-positive primary breast cancer in Vietnamese women after oophorectomy. (December 2017) - Haynes, Ben; Ginsburg, Ophira; Gao, Qiong; Folkerd, Elizabeth; Afentakis, Maria; Quang, Le; Han, Pham; Khoa, Pham; Dinh, Nguyen Van; To, Ta; Clemons, Mark; Smith, Ian; et al.
Abstract For premenopausal women with primary ER + breast cancer, oophorectomy (OvX) is an evidence-based cost-effective option and is standard treatment in many countries. However, there is virtually no data describing the effects of OvX on breast tumour biology. We therefore, characterised the endocrine and genome-wide transcriptional impact of OvX in 56 premenopausal women with ER + breast cancer for 2 weeks prior to mastectomy. Plasma estradiol concentrations decreased from 406 ± 41 to 20.7 ± 2.6 pmol/l (mean ± sem) 24 h after OvX, and to 8.1 ± 0.8 pmol/l 2 weeks later at mastectomy. Ki67 decreased in 33/36 (91.7%) tumours. The expression of 655 genes changed significantly (FDR < 1%) with an absolute mean fold-change (FC) ≥ 1.25 (257 up, 398 down). Archetypal oestrogen-regulated genes (TFF1, GREB1, PGR and PDZK1) showed large decreases in expression (FC = 0.20–0.69;p < 1e-6-1e-7). Proliferation-associated genes (e.g. TOP2A, AURKA and UBE2C) were also strongly downregulated (FC = 0.38–0.56;p < 1e-7) along with putative progesterone-regulated genes (e.g. FKBP4, MYB; FC = 0.64–0.68;p < 1e-4-1e-7). The gene expression changes did not differ according to HER2 status and correlated strongly with the changes reported previously after aromatase inhibitor (AI) treatment in postmenopausal women (rho = 0.55, p < 1e-04). However, after OvX the mean FC was significantly higher compared to AI (p < 1e-04). In conclusion, changes in tumoural gene expression after OvX were largely similar, but of a greater magnitude to those observed after AI in postmenopausal patients; however, OvX appeared to have a greater effect on progesterone-regulated genes than AI. Genetics: Ovary removal alters gene activity in breast tumours Surgical removal of the ovaries alters the expression of hundreds of genes in the tumour cells of premenopausal women with breast cancer. Ben Haynes from Royal Marsden Hospital in London, UK and colleagues characterised molecular changes in 56 premenopausal women from Vietnam with oestrogen receptor-positive breast cancer who underwent oophorectomies, a standard treatment for this patient population. They showed that blood levels of the hormone estradiol dropped precipitously following ovary-removal surgery. Levels of a protein that was indicative of tumour growth also went down, as did genes involved in regulating hormone signalling and cell proliferation. The results are consistent with those seen in postmenopausal women following treatment with an oestrogen-blocking drug, but oophorectomy had a more dramatic effect. The data could aid the search for predictive biomarkers of who stands to benefit most from ovary removal.